Estudo da Sedimentação de Partículas em Reservatórios Inclinados Utilizando a Técnica de Atenuação de Raios Gama - Schimicoscki, Raquel Stavale (2024)
Directional drilling of inclined wells, as opposed to conventional vertical drilling methods, enhances reservoir productivity, allowing for exploration of oil fields in challenging locations. Although drilling fluids experience sedimentation due to solid particles in the fluid formulation and cuttings from rock formation, especially in inclined wells, our understanding of the influence of wellbore inclination on sedimentation in these reservoirs remains insufficient. When the drilling fluid flow ceases, these solids naturally settle, potentially impeding the resumption of the process and causing equipment damage. In response to this challenge, this study aims to advance the understanding of the influence of wellbore inclination on solid sedimentation within if. To achieve this, suspensions (both Newtonian and non-Newtonian) were prepared, and the local volumetric solids concentration was monitored over time using the Gamma Ray Attenuation Technique at various positions within the test tube and at four different inclinations relative to the vertical axis (0°, 30°, 45°, and 60°). It was observed that the greater the inclination angle, the faster the sedimentation rate of solids. The phenomenon known as the Boycott effect becomes evident and significant during the suspension separation. Additionally, there is a change in the sedimentation dynamics related to the inclination of the container and the rheological characteristics of the fluids, associated with the Boycott effect and the gelification of biopolymer structures. Therefore, when opting for directional drilling, a careful balance must be struck between the advantages offered by inclined wells, such as increased productivity and reduced environmental impact, and the higher rate of solids sedimentation in drilling fluids.